Negative pole piece, secondary battery and preparation method of negative pole piece
By reasonably matching solid-state mixture in the negative electrode sheet of lithium-ion secondary battery, the problems of increasing internal resistance and degradation of rate performance after the battery energy density is increased, and high energy density, excellent rate performance and long cycle life are achieved.
Patent Information
- Application Number
- CN202411569736.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2024-12-27
AI Technical Summary
In lithium-ion secondary batteries, increasing the proportion of active substances in negative electrode sheets leads to an increase in battery energy density, but with the increase in internal resistance and degradation of rate performance, the cycle life is shortened.
By reasonably matching solid mixtures in the negative electrode coating, including negative electrode active substances, conductive agents, adhesives, dispersants and thickeners, satisfying specific mass fractions and polymerization relationships, controlling thickeners, dispersants and adhesives. The mass fraction of the contact agent is within a small range, which increases the ratio of the negative electrode active substance and the conductive agent, and enhances the energy density and cycle life of the battery.
The battery energy density, rate performance and cycle life are achieved while improving, ensuring good adhesion between the negative electrode coating and the current collector, and extending the battery service life.
Smart Images

Figure CN119208515A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of new energy technology, and in particular to a negative electrode sheet, a secondary battery, and a method for preparing the negative electrode sheet. Background Art
[0002] In recent years, lithium-ion secondary batteries have been widely used in electric passenger vehicles, commercial energy storage, communication energy storage and other fields, which have also put forward higher requirements for the energy density of lithium secondary batteries. Among them, increasing the proportion of active materials in the negative electrode is an important technical means to improve the energy density of batteries.
[0003] In the related art, a method to increase the proportion of active materials in the negative electrode plate is to reduce the amount of other solid materials in the negative electrode formula except the active materials. However, after adopting the negative electrode plate with such a formula, although the energy density of the battery is improved, it is also accompanied by an increase in the internal resistance of the battery and a decrease in the rate performance, which leads to a shortened cycle life of the battery. Summary of the invention
[0004] The present application provides a negative electrode plate, a secondary battery and a method for preparing a negative electrode plate to solve the problems of increased internal resistance of the battery, decreased rate performance, and shortened cycle life caused by increased energy density of the battery, thereby achieving simultaneous improvement of the energy density, rate performance and cycle life of the battery.
[0005] In a first aspect, the present application provides a negative electrode sheet, comprising a negative electrode current collector and a negative electrode coating; the negative electrode coating is coated on the negative electrode current collector, the negative electrode coating comprises a solid mixture, the solid mixture comprises a negative electrode active material, a conductive agent, a binder, a dispersant and a thickener, and the ratio of the negative electrode coating satisfies the relationship: Among them, m1 is the mass fraction of the thickener in the solid mixture, m2 is the mass fraction of the dispersant in the solid mixture, m3 is the mass fraction of the binder in the solid mixture, and p is the degree of polymerization of the thickener.
[0006] The negative electrode sheet provided in the first aspect satisfies the above relationship through the ratio of the negative electrode coating, so that the mass fraction of the thickener, dispersant and binder can be controlled within a smaller range, thereby increasing the mass fraction of the negative electrode active material and the conductive agent. When the amount of the conductive agent corresponding to different batteries meets the requirements, the amount of the negative electrode active material layer can be improved, thereby increasing the energy density of the battery. At the same time, the material viscosity of the negative electrode coating in the slurry state is relatively high, and the negative electrode slurry is not prone to sedimentation and unevenness. After the negative electrode slurry is coated on the negative electrode collector, the adhesion between it and the negative electrode collector is good. When the battery is cycled, the negative electrode coating is not easy to separate from the negative electrode collector. Therefore, the battery using the above-described negative electrode sheet also has a higher rate performance and a longer cycle life. It can be seen that when the above relationship is satisfied, the battery using the above-described negative electrode sheet can take into account high energy density, excellent rate performance and long cycle life.
[0007] In one possible design, the thickener includes at least one of sodium carboxymethyl cellulose, lithium carboxymethyl cellulose and sodium alginate, and the mass fraction of the thickener in the solid mixture satisfies 0%. <m1≤2%。
[0008] Through the above scheme, when the negative electrode sheet is in a slurry state, by using a certain amount of thickener, the viscosity of the negative electrode slurry can be appropriately increased, the fluidity can be reduced, the uniformity can be increased, and it is easy to coat and process. The negative electrode coating formed after the negative electrode slurry is dried has good adhesion to the negative electrode current collector, and the battery is not easy to swell. Controlling the mass fraction of the thickener within the above range can reduce the effect of the addition of the thickener on the mass fraction of other substances in the solid mixture, so that the battery can take into account high energy density, excellent cycle performance and long cycle life.
[0009] In a possible design, the polymerization degree of the thickener satisfies 100≤p≤5000.
[0010] Through the above scheme, the material viscosity and toughness of the negative electrode slurry can be controlled within a certain range, thereby improving the processability of the negative electrode slurry.
[0011] In a possible design, the polymerization degree of the thickener satisfies 100≤p≤2000.
[0012] Through the above scheme, the processability of the negative electrode slurry is further improved.
[0013] In a possible design, the dispersant includes at least one of polyacrylic acid, carboxymethyl chitosan, polyvinyl alcohol and modified materials thereof, and the mass fraction of the dispersant in the solid mixture satisfies 0%≤m2≤2%.
[0014] Through the above scheme, by using a certain amount of dispersant in the solid mixture, when the negative electrode plate is in a slurry state, the components of the solid mixture can be dispersed more evenly in the solvent. After the negative electrode slurry is dried on the surface of the negative electrode collector to become a negative electrode coating, the composition of each part of the negative electrode coating will also be more uniform, which is beneficial to improving the capacity and cycle performance of the battery.
[0015] In a possible design, the adhesive includes at least one of styrene-butadiene rubber, styrene-acrylate, polyacrylonitrile, polymethacrylate and modified materials thereof, and the mass fraction of the adhesive in the solid mixture satisfies 0%≤m3≤2%.
[0016] Through the above scheme, by using a certain amount of adhesive in the solid mixture, when the negative electrode plate is in a slurry state, the viscosity of the negative electrode slurry can be increased, thereby improving the processing performance of the negative electrode slurry. After the negative electrode slurry is dried on the surface of the negative electrode collector to become a negative electrode coating, the negative electrode coating will also be denser, and the adhesion between the negative electrode coating and the negative electrode collector is good and not easy to separate, thereby reducing the expansion of the negative electrode plate during use.
[0017] In one possible design, the ratio of the solid mixture satisfies the relationship:
[0018] Through the above scheme, the energy density of the battery using the negative electrode plate is further increased, the rate performance is better, and the cycle life is longer.
[0019] In one possible design, the conductive agent includes at least one of conductive carbon black, carbon nanotubes, graphite sheets, and graphene; and / or the negative electrode active material includes at least one of graphite, silicon oxide, silicon, silicon carbide, lithium titanate, and modified materials thereof.
[0020] Through the above scheme, in the negative electrode coating containing a conductive agent of any of the above materials and a negative electrode active material of any of the above materials, as long as the solid mixture satisfies the above relationship, the energy density, rate performance and cycle life of the battery can be improved simultaneously.
[0021] In a second aspect, the present application provides a secondary battery, comprising the negative electrode plate in any of the above embodiments.
[0022] Through the above scheme, the secondary battery has higher energy density, excellent rate performance and longer cycle life.
[0023] In a third aspect, the present application provides a method for preparing a negative electrode sheet, comprising the following steps:
[0024] The negative electrode active material, the conductive agent, the binder, the dispersant and the thickener are mixed to form a solid mixture, and the proportion of the solid mixture satisfies the relationship: Among them, m1 is the mass fraction of the thickener in the solid mixture, m2 is the mass fraction of the dispersant in the solid mixture, m3 is the mass fraction of the binder in the solid mixture, and p is the degree of polymerization of the thickener.
[0025] The solid mixture is mixed with a solvent to obtain a negative electrode slurry.
[0026] The negative electrode slurry is coated on both sides of the negative electrode current collector.
[0027] The negative electrode current collector coated with the negative electrode slurry is dried, cold pressed and cut to obtain a negative electrode sheet.
[0028] Through the above scheme, a solid mixture is first prepared, and after the components of the solid mixture are evenly mixed, a solvent is added to prepare the negative electrode slurry, so that the texture of the negative electrode slurry is more uniform. At the same time, the solid mixture satisfies the above relationship, so that the prepared negative electrode sheet can make the battery have a higher energy density, excellent rate performance and a longer cycle life when used.
[0029] The secondary battery and its beneficial effects provided in the above second aspect and each possible design of the above second aspect can refer to the beneficial effects brought by the above first aspect and each possible implementation method of the first aspect, and will not be repeated here. The preparation method of the negative electrode sheet provided in the above third aspect, the prepared negative electrode sheet can refer to the various embodiments of the negative electrode sheet of the above first aspect and its beneficial effects, and this application will not repeat them. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 A flow chart of a method for preparing a negative electrode plate provided in an embodiment of the present application. DETAILED DESCRIPTION
[0031] In order to make the invention purpose, technical scheme and beneficial technical effect of the present invention clearer, the present invention is further described in detail below in conjunction with examples and comparative examples. It should be understood that the embodiments described in this specification are only for explaining the present invention, not for limiting the present invention, and the formulas, proportions, etc. of the embodiments can be selected according to local conditions without substantial effect on the results.
[0032] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used in the specification of the application are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in the specification, claims and drawings of this application are intended to cover non-exclusive inclusions.
[0033] In the description of the present application, unless otherwise specified, "plurality" means more than two (including two), and similarly, "multiple groups" means more than two groups (including two).
[0034] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase "embodiments" in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0035] For simplicity, only some numerical ranges are explicitly disclosed herein. However, any lower limit can be combined with any upper limit to form an unambiguous range; and any lower limit can be combined with other lower limits to form an unambiguous range, and similarly, any upper limit can be combined with any other upper limit to form an unambiguous range. In addition, although not explicitly stated, each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unambiguous range.
[0036] The above summary of the invention of the present invention is not intended to describe each disclosed embodiment or each implementation in the present invention. The following description more specifically illustrates exemplary embodiments. In many places throughout the application, guidance is provided by a series of examples, which can be used in various combinations. In each example and, enumeration is only as a representative group and should not be interpreted as exhaustive.
[0037] Increasing the proportion of active materials in the negative electrode of a battery is an important technical means to increase the energy density of the battery. Increasing the proportion of active materials in conventional negative electrode sheets will inevitably reduce the amount of other solid materials in the negative electrode formula except for the active materials. After using the negative electrode sheet with this formula, although the energy density of the battery is improved, it is also accompanied by an increase in the internal resistance of the battery and a decrease in the rate performance, which leads to a shortened cycle life of the battery.
[0038] After research, the inventors found that the cause of the above problems is that other solid substances in the negative electrode formula except the active substance usually have the effect of increasing the viscosity, stability, dispersion uniformity of the negative electrode slurry (the state of the negative electrode coating before drying), and play a conductive role. Reducing these substances will lead to poor stability of the negative electrode slurry and easy sedimentation, which will lead to poor coating uniformity when the negative electrode slurry is coated on the negative electrode current collector, poor adhesion between the negative electrode coating and the current collector, etc., and will also lead to an increase in the internal resistance of the battery. All of the above will eventually lead to problems such as rapid expansion and growth of the battery during charging and discharging, poor rate performance and short cycle life.
[0039] Therefore, those skilled in the art have been seeking a method that can take into account the energy density, rate performance and cycle life of the battery.
[0040] In view of this, the present application provides a negative electrode plate and a secondary battery, which achieves the goal of increasing the proportion of active materials while effectively exerting the role of each component, thereby ensuring the energy density, rate performance and cycle life of the battery by reasonably associating and matching the components of the solid mixture in the negative electrode coating according to certain requirements and ratios. The details are explained below.
[0041] In a first aspect, the present application provides a negative electrode plate, the negative electrode plate comprising a negative electrode current collector and a negative electrode coating; the negative electrode coating is coated on the surface of the negative electrode current collector, the negative electrode coating comprises a solid mixture, the solid mixture comprises a negative electrode active material, a conductive agent, a binder, a dispersant and a thickener, and the ratio of the negative electrode coating satisfies the relationship: Among them, m1 is the mass fraction of the thickener in the solid mixture, m2 is the mass fraction of the dispersant in the solid mixture, m3 is the mass fraction of the binder in the solid mixture, and p is the degree of polymerization of the thickener.
[0042] The negative electrode current collector is one of the indispensable components of the negative electrode plate. It not only carries the negative electrode coating, but also collects and outputs the negative electrode current. The negative electrode current collector can be any material in the art that is suitable for use as a negative electrode current collector for lithium-ion batteries. For example, the negative electrode current collector can include but is not limited to metal foil, and more specifically can include but is not limited to copper foil or carbon-coated copper foil.
[0043] The negative electrode coating is coated on the surface of the negative electrode current collector and is used to conduct electrons under the infiltration of the electrolyte. The negative electrode coating is formed by drying the negative electrode slurry. The negative electrode slurry is a viscous substance formed by a mixture of a solid mixture and a solvent. The negative electrode slurry is coated on the surface of the negative electrode current collector. After drying, the solvent is evaporated and the remaining solid mixture adheres to the surface of the negative electrode current collector as the negative electrode coating.
[0044] The solid mixture in the embodiment of the present application includes a negative electrode active material, a conductive agent, a binder, a dispersant and a thickener, and the mass fraction of the entire solid mixture is recorded as 100%.
[0045] In some embodiments, the negative electrode active material includes at least one of graphite, silicon oxide, silicon, silicon carbide, lithium titanate and modified materials thereof.
[0046] In some embodiments, the conductive agent includes at least one of conductive carbon black, carbon nanotubes, graphite sheets, and graphene.
[0047] In some embodiments, the adhesive includes at least one of styrene-butadiene rubber, styrene-acrylate, polyacrylonitrile, polymethacrylate and modified materials thereof, and the mass fraction of the adhesive in the solid mixture satisfies 0%≤m3≤2%.
[0048] Specifically, the mass fraction of the adhesive may be 0, 0.6%, 1.2%, 1.5%, 1.8%, 2%, etc.
[0049] When the negative electrode sheet is in a slurry state, the adhesive can increase the viscosity of the negative electrode slurry, thereby improving the processing performance of the negative electrode slurry. After the negative electrode slurry dries on the surface of the negative electrode collector to become a negative electrode coating, the negative electrode coating will also be denser, and the adhesion between the negative electrode coating and the negative electrode collector is good and not easy to separate, thereby reducing the expansion of the negative electrode sheet during use and improving the charge and discharge performance of the battery.
[0050] When the mass fraction of the adhesive is within the above range, the mass fraction m1 of the thickener, the degree of polymerization P of the thickener and the mass fraction m2 of the dispersant are reasonably matched to meet the following conditions: The negative electrode slurry can have good processing performance, and the battery using the negative electrode sheet has high energy density, excellent cycle performance and long cycle life.
[0051] In some embodiments, the dispersant includes at least one of polyacrylic acid, carboxymethyl chitosan, polyvinyl alcohol and modified materials thereof, and the mass fraction of the dispersant in the solid mixture satisfies 0%≤m2≤2%.
[0052] Specifically, the mass fraction of the dispersant may be 0, 0.6%, 1.2%, 2%, etc.
[0053] When the negative electrode sheet is in a slurry state, the dispersant can make the components of the solid mixture disperse more evenly in the solvent. After the negative electrode slurry dries on the surface of the negative electrode collector to become a negative electrode coating, the composition of each part of the negative electrode coating will also be more uniform, which is beneficial to improve the capacity and cycle performance of the battery.
[0054] When the mass fraction of the dispersant is within the above range, the mass fraction m1 of the thickener, the degree of polymerization P of the thickener and the mass fraction m1 of the adhesive are reasonably matched to meet the following conditions: The negative electrode slurry can have good processing performance, and the battery using the negative electrode plate can also have high energy density, excellent cycle performance and long cycle life.
[0055] In some embodiments, the thickener includes at least one of sodium carboxymethyl cellulose, lithium carboxymethyl cellulose and sodium alginate, and the mass fraction of the thickener in the solid mixture satisfies 0%. <m1≤2%。
[0056] Specifically, the mass fraction of the thickener can be 0.1%, 0.3%, 0.5%, 0.8%, 1.5%, 2%, etc.
[0057] The thickener can appropriately increase the viscosity of the negative electrode slurry, reduce fluidity, increase uniformity, and facilitate coating and processing. The negative electrode coating formed after the negative electrode slurry is dried has good adhesion to the negative electrode current collector, and the battery is not prone to expansion.
[0058] Controlling the mass fraction of the thickener within the above range can reduce the effect of the addition of the thickener on the mass fractions of other substances in the solid mixture, which is beneficial for the battery to have high energy density, excellent cycle performance and long cycle life.
[0059] In the above embodiments, the mass fractions of the binder, dispersant and thickener are controlled respectively, so that the mass fractions of the conductive agent and the negative electrode active material in the solid mixture can be guaranteed, avoiding the situation where the conductive agent and the negative electrode active material are reduced too much due to the increase of the binder, dispersant and thickener, thereby providing a guarantee for the high energy density and low resistivity of the battery.
[0060] The degree of polymerization (DP) is an indicator of the molecular size of a polymer, which indicates the number of repeating units (or chain links) contained in the polymer macromolecule chain. The degree of polymerization has an important influence on the physical and chemical properties of the polymer, such as molecular weight, solubility, mechanical strength, etc. Generally, the higher the degree of polymerization of the thickener, the longer the linear structure of the molecule of the thickener. When the mass fraction of the thickener is constant, the viscosity and toughness of the negative electrode slurry will be better. Therefore, this application adds the degree of polymerization of the thickener as a parameter to the above formula.
[0061] In some embodiments, the degree of polymerization of the thickener satisfies 100≤p≤5000.
[0062] Specifically, the degree of polymerization P of the thickener may be 100, 200, 400, 1000, 2000, 4000, 5000, etc.
[0063] Through the above scheme, the material viscosity and toughness of the negative electrode slurry can be controlled within a certain range, thereby improving the processability of the negative electrode slurry.
[0064] It is understandable that when the relationship At the same time, when the polymerization degree of the thickener is too large, the mass fractions of the thickener, dispersant and binder in the solid mixture will be affected and reduced. If the mass fractions of each component are reduced significantly, the performance of the battery will be affected.
[0065] Therefore, in other embodiments, the polymerization degree of the thickener further satisfies 100≤p≤2000. When the polymerization degree of the thickener is within this range, in order to satisfy the above formula, the mass fractions of the binder, dispersant and thickener can be set more reasonably, and the processability of the negative electrode slurry can also be improved.
[0066] It is understandable that in the same negative electrode sheet, the mass fraction of the binder, the mass fraction of the dispersant, the mass fraction of the thickener, and the degree of polymerization of the thickener can all satisfy the ranges specified in the above embodiments, or only the mass fractions of one or two of the components can satisfy the corresponding ranges. All of them can increase the energy density of the battery to a certain extent, improve the processability of the negative electrode sheet, and increase the rate performance and cycle life of the battery.
[0067] The present application also provides a method for preparing a negative electrode sheet, such as Figure 1 As shown, the method for preparing the negative electrode sheet in the embodiment of the present application includes the following steps:
[0068] S100, the negative electrode active material, the conductive agent, the binder, the dispersant and the thickener are mixed to form a solid mixture, and the proportion of the solid mixture satisfies the relationship: Among them, m1 is the mass fraction of the thickener in the solid mixture, m2 is the mass fraction of the dispersant in the solid mixture, m3 is the mass fraction of the binder in the solid mixture, and p is the degree of polymerization of the thickener.
[0069] In the above steps, the negative electrode active material, conductive agent, adhesive, dispersant and thickener in the solid mixture can be reasonably matched as needed, and on the basis of satisfying the numerical range of the above formula, the formula The calculated values can specifically be 2.7, 3, 3.3, 3.6, 3.8, 4.2, 4.3, 4.4, 5, 9, etc.
[0070] S200, mixing the solid mixture with a solvent to obtain a negative electrode slurry.
[0071] S300 , coating the negative electrode slurry on both sides of the negative electrode current collector.
[0072] S400, drying, cold pressing and cutting the negative electrode current collector coated with the negative electrode slurry to obtain a negative electrode sheet.
[0073] It can be understood that in the above S400, after the negative electrode current collector coated with the negative electrode slurry is dried, the solvent in the negative electrode slurry evaporates, the negative electrode slurry becomes a negative electrode coating, and the solid mixture in the negative electrode coating has the same composition as the solid mixture in the negative electrode slurry.
[0074] In the above scheme, a solid mixture is first prepared, and after the components of the solid mixture are evenly mixed, a solvent is added to prepare the negative electrode slurry, so that the texture of the negative electrode slurry is more uniform. At the same time, the solid mixture satisfies the above relationship, so that the prepared negative electrode sheet can make the battery have a higher energy density, excellent rate performance and a longer cycle life when used.
[0075] The present application also provides a secondary battery, comprising the negative electrode plate in any of the above embodiments.
[0076] Since the negative electrode plate in the above embodiment is adopted, the secondary battery has a higher energy density, excellent rate performance and a longer cycle life.
[0077] The following describes the different ratio combinations of the above solid mixtures and their effects on the properties of the negative electrode sheet through multiple groups of examples and comparative examples.
[0078] The following examples more specifically describe the disclosure of the present invention, which are intended for illustrative purposes only, as various modifications and variations within the scope of the present disclosure are apparent to those skilled in the art. Unless otherwise stated, all mass fractions, percentages, and ratios reported in the following examples are by weight, and all reagents used in the examples are commercially available and can be used directly without further processing.
[0079] Example 1
[0080] (1) Preparation of positive electrode sheet
[0081] Lithium iron phosphate (positive electrode active material), carbon black (conductive agent), polyvinylidene fluoride (binder) are mixed with N-methylpyrrolidone (positive electrode solvent) in a mass ratio of 96.5%:1.5%:2% to obtain positive electrode slurry, in which the mass fraction of solid matter in the positive electrode slurry is 58%. The positive electrode slurry is coated on both sides of aluminum foil (positive electrode current collector), dried, cold pressed and cut to obtain positive electrode sheets.
[0082] (2) Preparation of negative electrode sheet
[0083] Graphite (negative electrode active material), carbon black SP (conductive agent), sodium carboxymethyl cellulose (thickener), polyacrylic acid (dispersant) and styrene-butadiene rubber (binder) are mixed with water in a mass ratio of 96.9%:0.5%:0.8%:1.2%:0.6% to obtain a negative electrode slurry, wherein the mass fraction of the solid matter in the negative electrode slurry is 50%. The negative electrode slurry is coated on both sides of a copper foil (negative electrode current collector), dried, cold pressed and cut to obtain a negative electrode sheet.
[0084] (3) Preparation of diaphragm
[0085] A polypropylene diaphragm is used with a thickness of 16 μm.
[0086] (4) Preparation of electrolyte
[0087] Dimethyl carbonate, ethylene carbonate and diethyl carbonate were mixed at a ratio of 1:1:1, and lithium hexafluorophosphate was added, wherein the concentration of the lithium hexafluorophosphate was 1.1 mol / L, to obtain an electrolyte.
[0088] (5) Assembly
[0089] The positive electrode sheet, negative electrode sheet, separator, electrolyte, aluminum-plastic film and other components are assembled into a soft-pack lithium-ion battery.
[0090] Example 2-Example 15 and Comparative Example 1-Comparative Example 5
[0091] The preparation process of the positive electrode sheet, the preparation process of the diaphragm, the preparation process of the electrolyte and the assembly process in Examples 2 to 15 and Comparative Examples 1 to 5 are the same as those in Example 1. The difference from Example 1 is that the mass ratios of graphite (negative electrode active material), carbon black SP (conductive agent), sodium carboxymethyl cellulose (thickener), polyacrylic acid (dispersant) and styrene-butadiene rubber (adhesive) in the preparation process of the negative electrode sheet in Example 1 are changed to the ratios listed in Tables 1 and 2 to prepare different negative electrode sheets, and then the above-mentioned negative electrode sheets are assembled with other components such as positive electrode sheets, electrolytes, diaphragms, aluminum-plastic films, etc. into different soft-pack lithium-ion batteries.
[0092] The negative electrode sheets or batteries prepared in the above-mentioned Examples 1 to 15 and Comparative Examples 1 to 5 were subjected to the following tests.
[0093] Testing Process
[0094] (1) Negative electrode slurry viscosity test
[0095] Test using a viscometer.
[0096] (2) Adhesion test between negative electrode coating and negative electrode current collector
[0097] The 180° peeling method is used to quantitatively measure the peeling strength. The free end of the negative electrode sheet is folded 180°, and the free end and the test end of the negative electrode sheet are clamped on the upper and lower clamps respectively. In the same environment, continuous peeling is performed using a tensile testing machine until the negative electrode current collector and the negative electrode coating are completely separated to obtain the peeling force value. The peeling force value is used to measure the bonding strength between the negative electrode coating and the negative electrode current collector. The larger the peeling force value, the greater the bonding strength, and vice versa.
[0098] (3) DC internal resistance DCR test
[0099] The battery was adjusted to 50% SOC (State of Charge) at 25°C, left for 1 hour, OCV1 was recorded, discharged at 3C for 10s, OCV2 was recorded, and DCR was calculated according to (OCV1-OCV2) / 3C×1000.
[0100] (4) Cycle life test
[0101] The battery was charged at 1C constant current and constant voltage at 25°C to 3.65V, cut off at 0.05C, left for 30min, discharged at 1C constant current, cut off at 2.0V, left for 30min after discharge, and repeated the charge and discharge steps until the capacity decayed to 80% of the first cycle capacity, and the number of cycles was recorded.
[0102] The data obtained from the above tests are recorded in Tables 1 and 2 below.
[0103] Table 1
[0104]
[0105] Table 2
[0106] Example 9 Example 10 Embodiment 11 Example 12 Example 13 Embodiment 14 Embodiment 15 Comparative Example 4 Comparative Example 5 m1 / % 0.3 0.3 0.5 0.3 1.5 2 0.3 0.3 2.5 m2 / % 2 1.2 0 0 0 0 1.2 0 0 m3 / % 0 0 1.8 1.8 1.5 1.2 0 1.8 1.8 p 100 400 400 1000 100 100 100 100 400 <![CDATA[(pm1) / 100+2m2+m3]]> 4.3 3.6 3.8 4.8 3 3.2 2.7 2.1 11.8 Conductive agent SP / % 0.5 0.5 0.5 0.5 0.5 0.5 0.5 0.5 0.5 graphite / % 97.2 98 97.2 97.4 96.5 96.3 98 97.4 95.2 Slurry viscosity / mPa·s 4330 5760 6800 7300 8000 10050 2600 850 31000 Peel force / N 0.62 0.4 0.56 0.6 0.5 0.47 0.25 0.3 0.74 DC internal resistance / mΩ 13.6 13.5 14.7 15 15.4 16.1 14.5 15.1 18 Cycle life / times 3510 2900 3200 3300 2800 2690 2410 2300 1760
[0107] It should be noted that in the above table, the energy density of the battery is proportional to the percentage of graphite (negative electrode active material). The higher the percentage of graphite, the higher the energy density of the battery. Generally, the higher the energy density of the battery, the better.
[0108] The slurry viscosity is used to measure the processability of the negative electrode slurry. Usually, if the slurry viscosity of the negative electrode slurry is too high, the slurry may be difficult to mix evenly, difficult to apply evenly, and difficult to apply quantitatively, resulting in poor processability of the negative electrode slurry. If the slurry viscosity of the negative electrode slurry is too low, the slurry fluidity may be too large, and the solid mixture in the slurry may settle. These problems also reduce the processability of the negative electrode slurry and cause the problem of uneven coating of the negative electrode slurry. Therefore, it is better for the viscosity of the negative electrode slurry to be moderate. In this slurry viscosity test, the viscosity of the negative electrode slurry that is easy to process is 3000-16000mPa·s. It is understandable that when the test conditions change, the slurry viscosity range suitable for processing may vary.
[0109] The peeling force value reflects the ease of peeling between the negative electrode coating and the negative electrode current collector, and is used to measure the bonding strength between the negative electrode coating and the negative electrode current collector. The larger the peeling force value, the greater the bonding strength, and vice versa. In this test, the peeling force is best within 0.35-0.7N. It is understandable that when the test conditions change, the optimal range of the peeling force value may be different.
[0110] It can be seen from Examples 1-15 that when the mass fractions of the binder, dispersant, and thickener in the negative electrode coating and the degree of polymerization of the thickener are within an appropriate range and conform to the relationship listed in the present invention, the energy density of the battery can be improved by reasonably matching the amount of each material and the degree of polymerization of the thickener. At the same time, the processability of the negative electrode slurry of the negative electrode plate in the manufacturing process is improved, ensuring that the battery has a smaller DC internal resistance, excellent cycle performance and a longer cycle life.
[0111] It can be seen from Example 1 to Example 8 in Table 1 that when the overall amount of inactive substances is reduced, the relationship and parameter ranges listed in the present invention can be satisfied by adjusting the amount of one of the materials or the degree of polymerization P, such as only adjusting the amount of thickener m1 in Examples 2 and 3, only adjusting the amount of dispersant m2 in Examples 6 and 7, only adjusting the degree of polymerization p of the thickener in Examples 3 to 5, and only adjusting the amount of adhesive m3 in Examples 7 and 8. The amounts of several materials and the degree of polymerization P of the thickener can also be adjusted to satisfy the relationship and parameter ranges listed in the present invention. The above methods can achieve the satisfaction of the relationship and parameter ranges listed in the present invention, and The effect is to increase the proportion of active material graphite, thereby increasing the energy density of the battery. At the same time, the viscosity of the negative electrode slurry is ensured to be within the processable range without reducing the processing capacity. The adhesion between the prepared active coating of the electrode and the current collector is stable, and the internal resistance of the battery is reduced and the cycle life is increased. In addition, in the process of preparing the negative electrode, it is found that the coating weight of the negative electrode slurry per unit area of the negative electrode current collector is more uniform, which will make the battery's charge and discharge performance and rate performance more excellent.
[0112] It can be seen from Examples 9 to 15 in Table 2 that when the amount of inactive substance is reduced and the amount of dispersant m2 or the amount of adhesive m3 is at an extreme value, the relationship listed in the present application can also be satisfied by reasonably matching the design and amount of other materials. and the range of each parameter requirement, such as in Examples 9 and 10, when the amount of adhesive m3 is 0, the amount of dispersant m2 is adjusted, and in Examples 11-14, when the amount of dispersant m2 is 0, the amount of thickener m1, the degree of polymerization p of the thickener and the amount of adhesive m3 are adjusted. The above methods can satisfy the relationship listed in this application. It can also increase the proportion of active material graphite and ensure that the viscosity of the negative electrode slurry is within the processable range. The final battery has the beneficial effects of high energy density and long cycle life.
[0113] It can be seen from Comparative Examples 1-5 in Table 1 and Table 2 that, when the relationship formula listed in the present invention is not satisfied, no matter whether the composition and design of each material are within the range, it will have an adverse effect on the performance of the battery.
[0114] For example, it can be seen from Comparative Examples 1 and 5 that The result is greater than the relationship listed in the present application, which will lead to high viscosity of the negative electrode slurry, greater adhesion between the negative electrode coating and the current collector, too high internal resistance of the battery, and shortened cycle life of the battery.
[0115] It can be seen from Comparative Examples 3 and 4 that The result is smaller than the relationship listed in the present application, which will lead to low viscosity of the negative electrode slurry, poor slurry processability, precipitation of solid matter, and poor adhesion between the negative electrode coating and the current collector, which will affect the cycle life of the battery. This may be related to the fact that in the later stage of battery use, the negative electrode coating of the negative electrode sheet is separated from the negative electrode current collector, and electron transmission is blocked.
[0116] It can be seen from Comparative Example 2 that when the dosage parameter m3 of the selected adhesive is not within the range, the adhesion between the negative electrode coating and the current collector is too large, resulting in excessive internal resistance of the battery and a short cycle life of the battery.
[0117] In addition, in the above-mentioned Examples 1 to 15, the slurry viscosity in Example 5 is much greater than the slurry viscosity in other examples on the basis of meeting the requirements, and the cycle life of the battery in Example 15 is slightly lower than the batteries in other examples on the basis of meeting the requirements. It can be seen that in order to make the battery have further excellent performance in these three aspects while taking into account high energy density, excellent rate performance and long cycle life, in some embodiments, the mass fraction m1 of the thickener in the solid mixture, the mass fraction m2 of the dispersant in the solid mixture, the mass fraction m3 of the adhesive in the solid mixture, and the degree of polymerization p of the thickener can be further made to meet
[0118] In summary, the embodiment of the present application makes the ratio of the negative electrode coating meet The total mass fraction of the thickener, dispersant and binder can be controlled within a smaller range, thereby increasing the mass fraction of the negative electrode active material and the conductive agent. When the amount of conductive agent corresponding to different batteries meets the requirements, the amount of the negative electrode active material layer can be increased, thereby increasing the energy density of the battery. At the same time, the material viscosity of the negative electrode coating in the slurry state is relatively high, and the negative electrode slurry is not prone to sedimentation and unevenness. After the negative electrode slurry is coated on the negative electrode collector, the adhesion between it and the negative electrode collector is good. When the battery is cycled, the negative electrode coating is not easy to separate from the negative electrode collector. The battery using the above-described negative electrode pole piece also has a higher rate performance and a longer cycle life. In short, under the condition that the above relationship is satisfied, the battery using the above-mentioned negative electrode pole piece can take into account high energy density, excellent rate performance and long cycle life.
Claims
1. A negative electrode plate, characterized in that: include: Anode current collector; A negative electrode coating, the negative electrode coating is applied to the negative electrode current collector, the negative electrode coating comprises a solid mixture, the solid mixture comprises a negative electrode active material, a conductive agent, a binder, a dispersant and a thickener, and the ratio of the negative electrode coating satisfies the relationship: Wherein, m1 is the mass fraction of the thickener in the solid mixture, m2 is the mass fraction of the dispersant in the solid mixture, m3 is the mass fraction of the adhesive in the solid mixture, and p is the degree of polymerization of the thickener.
2. The negative electrode sheet according to claim 1, characterized in that: The thickener comprises at least one of sodium carboxymethyl cellulose, lithium carboxymethyl cellulose and sodium alginate, and the mass fraction of the thickener in the solid mixture satisfies 0%. <m1≤2%。 3. The negative electrode sheet according to claim 1, characterized in that: The polymerization degree of the thickener satisfies 100≤p≤5000.
4. The negative electrode sheet according to claim 3, characterized in that: The polymerization degree of the thickener satisfies 100≤p≤2000.
5. The negative electrode sheet according to claim 1, characterized in that: The dispersant includes at least one of polyacrylic acid, carboxymethyl chitosan, polyvinyl alcohol and modified materials thereof, and the mass fraction of the dispersant in the solid mixture satisfies 0%≤m2≤2%.
6. The negative electrode sheet according to claim 1, characterized in that: The adhesive comprises at least one of styrene-butadiene rubber, styrene-acrylate, polyacrylonitrile, polymethacrylate and modified materials thereof, and the mass fraction of the adhesive in the solid mixture satisfies 0%≤m3≤2%.
7. The negative electrode sheet according to claim 1, characterized in that: The proportion of the solid mixture satisfies the relationship:
8. The negative electrode sheet according to any one of claims 1 to 7, characterized in that: The conductive agent includes at least one of conductive carbon black, carbon nanotubes, graphite sheets, and graphene; and / or the negative electrode active material includes at least one of graphite, silicon dioxide, silicon, silicon carbide, lithium titanate, and modified materials thereof.
9. A secondary battery, characterized in that: The invention comprises the negative electrode sheet as described in any one of claims 1 to 8.
10. A method for preparing a negative electrode sheet, characterized in that: include: The negative electrode active material, the conductive agent, the binder, the dispersant and the thickener are mixed to form a solid mixture, and the proportion of the solid mixture satisfies the relationship: Wherein, m1 is the mass fraction of the thickener in the solid mixture, m2 is the mass fraction of the dispersant in the solid mixture, m3 is the mass fraction of the adhesive in the solid mixture, and p is the degree of polymerization of the thickener; Mixing the solid mixture with a solvent to obtain a negative electrode slurry; Applying the negative electrode slurry on both sides of the negative electrode current collector; The negative electrode current collector coated with the negative electrode slurry is dried, cold pressed, and cut to obtain a negative electrode sheet.
Citation Information
Cited By
Negative electrode sheet, secondary battery, and manufacturing method for negative electrode sheet
WO2026097913A1
